Challenges and solutions for sustainable food systems: The potential of home hydroponics - Sousa, Rui de (2024)
The global food system is currently facing significant challenges that make it unsustainable and environmentally harmful. These challenges not only threaten food security but also have severe negative impacts on the environment. Efforts have been made to reform agrifood systems and align them with the built environment, but emerging obstacles have revealed the weaknesses in these systems, particularly in less self-sufficient countries. This review outlines the primary environmental problems associated with global agrifood systems and the challenges in promoting food security. It emphasizes that the increasing global population and urbanization need rational and equitable changes in food systems, including production, distribution, storage, and consumption. These changes should aim to minimize environmental impacts by protecting and efficiently utilizing natural resources such as air, water, soil, and biodiversity, reducing food loss and waste, and mitigating pollution that contributes to ecosystem degradation and climate change. In this context, hydroponics emerges as a sustainable, plant-based food production technique that can be employed as a solution in urban areas. It can be implemented in domestic microproduction systems, serving as a complementary alternative to conventional food production methods. This study also provides insights into the challenges that need to be addressed in order to enhance home hydroponic systems. The integration of hydroponics into urban food production offers the potential to tackle both food security and environmental sustainability issues, providing a path toward more resilient and efficient food systems.